Detection of aflatoxin M1 in raw cow milk in Perak district (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Milk and dairy products are potentially contaminated with aflatoxin M1 (AFM1), especially in tropical and subtropical regions like Malaysia. This study aimed to detect the concentration of AFM1 in raw cow milk samples by ELISA method. A total of 46 samples of raw cow milk were received from four Milk Collection Centres (MCC) in Perak (A, B, C and D). 13.0% of the samples examined were found to exceed the European Commission (EC) 0.05 µg/kg maximum limit, with samples from MCC B and D accounting for 25.0% and 21.1% respectively. Statistical analysis showed that there was a significant difference in the mean concentration of AFM1 between the four MCCs at p
Keywords: aflatoxin M1; raw cow milk; Perak district